Characteristics of onset of boiling under downward flow condition - Takatoshi KAMEDA; Takeyuki AMI; Hisashi UMEKAWA (Nihon Kikai Gakkai ronbunshu, 2020)
Understanding of the onset of boiling plays an important role in the design of boiling equipment. Therefore, many studies have been reported so far, but most of these concerned with the upward flow condition. Moreover, the onset of boiling condition in downward flow is complex due to stagnant and/or reverse bubble caused by buoyancy force on thermal-non-equilibrium flow field, thus the correlation for upward flow cannot be applied directly to downward flow. The purpose of this study is to clarify the characteristics of onset of boiling under downward flow. In the experiment, the onset of boiling condition was measured by using several size of test sections under upward and downward flow conditions. Experimental results expressed the typical two kinds of tendencies, i.e. thermal dominant and the thermal-fluid dominant conditions, with the difference of heating length of test section. In the case of thermal-fluid dominant condition, the difference between upward and downward flows was also clearly observed. On the basis of experimental results, the modified Bowring’s and modified Levy’s correlations are proposed for each region, and these modified correlations show good agreements with the experimental results in each condition.